Bone Marrow Niches and Tumour Cells: Lights and Shadows of a Mutual Relationship - Granata, Valentina; Crisafulli, Laura; Nastasi, Claudia; Ficara, Francesca; Sobacchi, Cristina (Frontiers in Immunology, 2022)
The bone marrow (BM) niche is the spatial structure within the intra-trabecular spaces of spongious bones and of the cavity of long bones where adult haematopoietic stem cells (HSCs) maintain their undifferentiated and cellular self-renewal state through the intervention of vascular and nervous networks, metabolic pathways, transcriptional and epigenetic regulators, and humoral signals. Within the niche, HSCs interact with various cell types such as osteoblasts, endothelial cells, macrophages, and mesenchymal stromal cells (MSCs), which maintain HSCs in a quiescent state or sustain their proliferation, differentiation, and trafficking, depending on body needs. In physiological conditions, the BM niche permits the daily production of all the blood and immune cells and their admittance/ingress/progression into the bloodstream. However, disruption of this delicate microenvironment promotes the initiation and progression of malignancies such as those included in the spectrum of myeloid neoplasms, also favouring resistance to pharmacological therapies. Alterations in the MSC population and in the crosstalk with HSCs owing to tumour-derived factors contribute to the formation of a malignant niche. On the other hand, cells of the BM microenvironment cooperate in creating a unique milieu favouring metastasization of distant tumours into the bone. In this framework, the pro-tumorigenic role of MSCs is well-documented, and few evidence suggest also an anti-tumorigenic effect. Here we will review recent advances regarding the BM niche composition and functionality in normal and in malignant conditions, as well as the therapeutic implications of the interplay between its diverse cellular components and malignant cells.